The DSM-5 criteria, level of arousal and delirium diagnosis: Inclusiveness is safer - CUNNINGHAM, COLM (My University, 2014)
Background Delirium is a common and serious problem among acutely unwell persons. Alhough linked to higher rates of mortality, institutionalisation and dementia, it remains underdiagnosed. Careful consideration of its phenomenology is warranted to improve detection and therefore mitigate some of its clinical impact. The publication of the fifth edition of the Diagnostic and Statistical Manual of the American Psychiatric Association (DSM-5) provides an opportunity to examine the constructs underlying delirium as a clinical entity. Discussion Altered consciousness has been regarded as a core feature of delirium; the fact that consciousness itself should be physiologically disrupted due to acute illness attests to its clinical urgency. DSM-5 now operationalises `consciousness¿ as `changes in attention¿. It should be recognised that attention relates to content of consciousness, but arousal corresponds to level of consciousness. Reduced arousal is also associated with adverse outcomes. Attention and arousal are hierarchically related; level of arousal must be sufficient before attention can be reasonably tested. Summary Our conceptualisation of delirium must extend beyond what can be assessed through cognitive testing (attention) and accept that altered arousal is fundamental. Understanding the DSM-5 criteria explicitly in this way offers the most inclusive and clinically safe interpretation.
PUBLISHED
Keywords: Delirium; Consciousness; Arousal; Attention; Diagnostic and Statistical Manual of Mental Disorders; Delirium; Consciousness; Arousal; Attention; Diagnostic and Statistical Manual of Mental Disorders